2009
DOI: 10.4238/vol8-3gmr567
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the mite Varroa destructor (Acari: Varroidae) collected from honey bees Apis mellifera (Hymenoptera, Apidae) in the State of Santa Catarina, Brazil

Abstract: ABSTRACT. The mite Varroa destructor is an ectoparasite that is considered a major pest for beekeeping with European honey bees. However, Africanized bee colonies are less threatened by this ectoparasite, because infestation levels remain low in these bees. The low reproductive ability of female mites of the Japanese biotype (J), introduced to Brazil early in the 1970s was initially considered the main factor for the lack of virulence of this parasite on Africanized bees. In other regions of the world where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
3
25
0
2
Order By: Relevance
“…The presence of Varroa mites in Venezuela and Chile is recent: it was detected in Venezuela in 1991 (Principal et al 1991) and in Chile in 1992 (Casanova and Perruolo 1992). Current studies have demonstrated that the Korean haplotype is cosmopolite in SA (Strapazzon et al 2009;Maggi et al 2012), to the point that the Japanese haplotype is nearly absent in SA countries. The island of Fernando de Noronha (Brazil) is the exception, where Italian bees were introduced into colonies that had been transported from mainland Brazil in 1984 (De Jong andSoares 1997).…”
Section: Varroosismentioning
confidence: 97%
“…The presence of Varroa mites in Venezuela and Chile is recent: it was detected in Venezuela in 1991 (Principal et al 1991) and in Chile in 1992 (Casanova and Perruolo 1992). Current studies have demonstrated that the Korean haplotype is cosmopolite in SA (Strapazzon et al 2009;Maggi et al 2012), to the point that the Japanese haplotype is nearly absent in SA countries. The island of Fernando de Noronha (Brazil) is the exception, where Italian bees were introduced into colonies that had been transported from mainland Brazil in 1984 (De Jong andSoares 1997).…”
Section: Varroosismentioning
confidence: 97%
“…Importantly, the Island of Fernando de Noronha is still parasitized by the original Japanese mite haplotype that was introduced from mainland Brazil when the island's honeybee population was first established (Strapazzon et al 2009). The presence of the less virulent Japanese mite haplotype on the island could explain how this honeybee population manages to survive with uncontrolled Varroa mite infestation.…”
Section: Island Of Fernando De Noronhamentioning
confidence: 99%
“…No Brasil, as abelhas africanizadas apresentam algumas características que favorecem a resistência ao ácaro, inclusive elevada infertilidade do parasita nesse biótipo (Rosenkranz, 1999), o que pode explicar os baixos níveis de infestação observados no país (Strapazzon et al, 2009;.…”
Section: Patógenos Parasitas E Predadoresunclassified